Efektivitas Aplikasi Sistem Informasi Desa Mendalo Indah (SIMENDAH) dalam Meningkatkan Pelayanan Publik pada Pemerintah Desa Mendalo Indah (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study aims to analyze the Effectiveness of the Mendalo Indah Village Information System Application (Simendah) in improving public services at the Mendalo Indah Village Government. The study employs a qualitative method with a descriptive research type and data collection techniques consisting of observation, interviews, and documentation. The findings indicate that the Simendah application is considered ineffective in enhancing public services, as several indicators have not been fulfilled. In terms of productivity, the objectives of the application have not been fully achieved, as many residents have not utilized the application, resulting in no significant increase in the number of services processed annually. In terms of adaptability, many residents still prefer to handle administrative documents conventionally, indicating a low level of acceptance of digital systems. In terms of development, the application is not yet mature, as it often experiences errors and remains vulnerable to hacking. Furthermore, the effectiveness of the application is constrained by limited facilities and infrastructure, the low quality of human resources, the lack of community understanding of the application’s use, and the minimal participation of residents in utilizing the digital services.